Machiavelli's Platonic problems : neoplatonism, eros, mythmaking, and philosophy in Machiavellian thought /: neoplatonism, eros, mythmaking, and philosophy in Machiavellian thought. (2021) - Bogiaris, Guillaume
No abstract available